Nutritional Determinants and Molecular Insights into Anemia among Boarding School Adolescents - Kiky Martha Ariesaka; Lintang Widya Sishartami; Anditri Weningtyas; Moh. Mirza Nuryady (Jurnal Kesehatan Masyarakat, 2026)
Introduction: Anemia remains a significant public health problem among adolescents in developing countries such as Indonesia. Female adolescents are more vulnerable due to menstrual blood loss and increased iron needs during growth, while dietary diversity and beverage habits may further influence anemia risk. Aim: This study aimed to analyze factors associated with anemia, including gender, diet quality, and tea or coffee consumption, and to explore their molecular relevance using a bioinformatics approach. Methods: A cross-sectional study was conducted among 199 adolescents (105 males, 94 females) aged 12–17 years in a boarding school in Malang, Indonesia. Data collection included hemoglobin measurement, anthropometric assessment, and a Food Frequency Questionnaire (FFQ). Statistical analysis was performed using Chi-square and logistic regression, while bioinformatics analysis employed STRING, Cytoscape, and ShinyGO to identify key genes and pathways. Results: Female gender (AOR = 6.595; p < 0.001), adequate diet (AOR = 0.184; p = 0.012), and tea/coffee intake (AOR = 7.532; p < 0.001) were significant predictors of anemia. Bioinformatics analysis identified SLC11A2, TFRC, and HAMP as key genes regulating ferroptosis and mineral absorption pathways. Conclusions: Gender, dietary quality, and tea or coffee consumption significantly influence anemia in adolescents.